BIG DATA CHARACTERISTICS, CLASSIFICATION AND CHALLENGES - A REVIEW - et. al., K S Ananda Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The data is an assest of great importance for any organization. Big data is the large collection of data; it includes different types of data collected from banking, e-commerce, insurance, manufacturing, social media and business data etc . Big data Analytics is the examine the bulk amount of data. To deal the large amount of data traditional techniques are inefficient, less accuracy and less performance. Big data technologies are face the large and complex data in efficient manner. Hadoop technology is designed to process the Big data. Hadoop is an open source software used for distributed processing of big data among the servers. Parallelism technique is used to process the large amount of data. Currently the big data analytics is the one of the research area and development. Nowadays the big data has great importance and good choice for new researchers. The paper's main purpose is to discuss the features of big data and the technological challenges.